PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - Syahriani Syahriani (Jurnal Biotek, 2017)
The cooperative learning of Team Assisted Individualization (TAI) type is a form of learning of a combination between cooperative learning and individual learning. Students stay in groups but each of them study based on his or her speed and ability. This study aims at examining (1) the improvement of activity in learning Biology of grade XI IPA Students at Madrasah Aliyah Madani Alauddin Pao-Pao through the application of cooperative learning of TAI type, and (2) the improvement learning outcomes on Biology of grade XI IPA students at Madrasah Aliyah Madani Alauddin Pao-Pao through the application of cooperative learning of TAI type. This study is a classroom action research. The subject of the study was 20 grade XI IPA students at Madrasah Aliyah Madani Alauddin Pao-Pao. Data were collected by employing questionnaire of observation sheet on activity of students, and the test of learning outcomes. Data were analyzed quantitatively in percentage. The results reveal (1) the cooperative learning of TAI type can improve the activity of students of grade XI IPA at Madrasah Aliyah Madani Alauddin Pao-Pao with the mean score 44.90 in cycle I and improved to 75.00 in cycle II, and (2) the cooperative learning of TAI type can improve Biology learning outcomes of grade XI IPA students at Madrasah Aliyah Madani Alauddin Pao-Pao with the percentage of completeness 65 % in cycle I and improved to 90% in cycle II. The conclusion of this study is the cooperative learning if TAI type can improve motivation, activity, and learning outcomes of Biology of grade XI IPA students at Madrasah Aliyah Madani Alauddin Pao-Pao in Gowa.